Meta‐analysis of suicide rates among psychiatric in‐patients. (5th January 2015) - Walsh, G.; Sara, G.; Ryan, C. J.; Large, M.
<x xml:space="preserve">Abstract</x> Objective To examine factors associated with the number of psychiatric admissions per in‐patient suicide and the suicide rate per 100 000 in‐patient years in psychiatric hospitals. Method Random‐effects meta‐analysis was used to calculate pooled estimates, and meta‐regression was used to examine between‐sample heterogeneity. Results Forty‐four studies published between 1945 and 2013 reported a total of 7552 in‐patient suicides. The pooled estimate of the number of admissions per suicide calculated using 39 studies reporting 150 independent samples was 676 (95% CI: 604–755). Recent studies tended to report higher numbers of admissions per suicide than earlier studies. The pooled estimate of suicide rates per 100 000 in‐patient years calculated using 27 studies reporting 95 independent samples was 147 (95% CI: 138–156). Rates of suicide per 100 000 in‐patient years tended to be higher in more recent samples, in samples from regions with a higher whole of population suicide rate, in samples from settings with a shorter average length of hospital stay and in studies using coronial records to define suicide. Conclusion Rates of in‐patient suicide in psychiatric hospitals vary remarkably and are disturbingly high. Further research might clarify the extent to which patient factors and the characteristics of in‐patient facilities contribute to the unacceptable mortality in psychiatric hospitals.